Biomechanical characterisation of ovine spinal facet joint cartilage - Abd Latif, M.J.; Jin, Z.; Wilcox, R.K. (Elsevier Ltd., 2012)
The spinal facet joints are known to be an important component in the kinematics and the load transmission of the spine. The articular cartilage in the facet joint is prone to degenerative changes which lead to back pain and treatments for the condition have had limited long term success. There is currently a lack of information on the basic biomechanical properties of the facet joint cartilage which is needed to develop tissue substitution or regenerative interventions. In the present study, the thickness and biphasic properties of ovine facet cartilage were determined using a combination of indentation tests and computational modelling. The equilibrium biphasic Young’s modulus and permeability were derived to be 0.76 MPa and 1.61 m4/(Ns) respectively, which were within the range of cartilage properties characterised from the human synovial joints. The average thickness of the ovine facet cartilage was 0.52 mm, which was measured using a needle indentation test. These properties could potentially be used for the development of substitution or tissue engineering interventions and for computational modelling of the facet joint. Furthermore, the developed method to characterise the facet cartilage could be used for other animals or human donors.